2018
DOI: 10.1038/s41598-018-25390-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticles with antioxidant capabilities and gadolinium integration for MRI contrast enhancement

Abstract: The chelating gadolinium-complex is routinely used as magnetic resonance imaging (MRI) -contrast enhancer. However, several safety issues have recently been reported by FDA and PRAC. There is an urgent need for the next generation of safer MRI-contrast enhancers, with improved local contrast and targeting capabilities. Cerium oxide nanoparticles (CeNPs) are designed with fractions of up to 50% gadolinium to utilize the superior MRI-contrast properties of gadolinium. CeNPs are well-tolerated in vivo and have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 63 publications
11
90
1
Order By: Relevance
“…[33][34][35] Antioxidants could be harmful per se, because of pro-oxidant activity. [36][37][38] For example, Srinivas et al suggested that acute exposure of CNPs through inhalation route may induce cytotoxicity via oxidative stress and may lead to a chronic inflammatory response. 39 Adebayo et al also showed that administration of 100-300 mg/kg CNPs thrice in a week for 5 consecutive weeks to mice induces testicular dysfunction via disruption of antioxidant/oxidant balance and endocrine suppression.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Antioxidants could be harmful per se, because of pro-oxidant activity. [36][37][38] For example, Srinivas et al suggested that acute exposure of CNPs through inhalation route may induce cytotoxicity via oxidative stress and may lead to a chronic inflammatory response. 39 Adebayo et al also showed that administration of 100-300 mg/kg CNPs thrice in a week for 5 consecutive weeks to mice induces testicular dysfunction via disruption of antioxidant/oxidant balance and endocrine suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have investigated and reported on the precipitation method for the synthesis of cerium oxide nanoparticles using various chemical ingredients. Some of the reagents that are used in the precipitation method include precursors such as cerium nitrate hexahydrate and sodium hydroxide [26,65,66]. Metal oxide powders are acquired by the addition of a ligand such as ammonia into solution of metal ions.…”
Section: Precipitation Methodsmentioning
confidence: 99%
“…Changes in nanoparticle sizes directly affect their characteristics and behavior. These changes influence biological parameters such as the biological half-life, diffusivity, and immunogenicity [26]. Decreases in the sizes of the particles increases the surface area to volume ratio.…”
Section: Size Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare earth nanoparticles (RENPs), as a type of articial nanoparticles, have excellent physicochemical properties and extensive applications, and are considered as a treasury of opportunities for new light sources, magnetic sources, energy sources, and materials. [5][6][7] With the widespread use of RENPs, the potential risks of their accumulation and migration in the environment are expanding. 8 The phytotoxicity of RENPs has been conrmed by some laboratory simulations.…”
Section: Introductionmentioning
confidence: 99%